Penentu kepimpinan berorientasikan pekerja dantugas terhadap kejayaan projek di kalangan kontraktor binaan di kuantan pahang - Noraini, Misran (2012)
The construction industry is one of the most important sectors that contribute to the economy and a catalyst for other industries.However in recent years,there are several construction projects not being completed on time, scope and within budget due to several factors.Based on previous studies,this problem arises due to the weakness of human factors,especially from the aspect of ineffective leadership and weak leadership practiced by project managers and contractors in managing the project team. Many researchers have made a study and focuses on the importance of leadership as a key to the success of the project. Accordingly,this study is to identify the leadership characteristics that influence the success of the project. The objective of this study also to examine the influence and the relationship between employee-oriented and taskoriented leadership to the success of the project among contractors in the construction industry.The study also describes the leadership characteristics that influence the success of the project based on the contractor’s demographic background.The sample of this study were involved contractors class A, B, C, D, E and F,which involved in construction projects in the district of Kuantan Pahang. The sampling method using stratified random sampling.The sample size was about 278 contractors selected from the 993 contractors registered with the Contractors Service Centre (PKK) in Pahang.Data collection is of primary data obtained through questionnaire.This study answered the five main questions using factor analysis,one sample t-test,Pearson correlation analysis,one-way analysis of variance (ANOVA) and multiple regression analysis.The results of this study has shown that the overall level of the characteristics of employeeoriented and task-oriented leadership among contractors in Kuantan, Pahang is high in terms of providing services,develop employees, sharing power and decision making,visionary,leading and project team building.The results of Pearson correlation analysis proved that employee-oriented and task-oriented leadership was positively correlated with the success of a project in which the characteristics of visionary leadership has the highest correlation relationship to the success of the project, followed by project team building,leading,develop employees, providing services and finally is sharing power and decision making.Meanwhile,one-way analysis of variance showed that there were significant differences based on the four demographic factors of age,education level,experience and leadership training to the success of the project.These factors significantly influence the success of the project. Results of multiple regression analysis produced a model that can predict the success of the project based on the characteristics of employee-oriented and task-oriented leadership.The results of multiple regression analysis showed that the characteristics of visionary leadership is the most significant variable in determining the success of the project,followed by team building.In conclusion,this study developed a model framework results from this analysis indicates that project success is significantly influenced by the characteristics of the task-oriented leadership in terms of visionary and team building.Regression equation obtained for a model is a Successful Project = 2.160 + 0.360 (Visionary)+0.318(Project Team Building).